2021
DOI: 10.1111/1365-2664.13836
|View full text |Cite
|
Sign up to set email alerts
|

Forest regeneration can positively contribute to local hydrological ecosystem services: Implications for forest landscape restoration

Abstract: Governments are increasingly committing to significant forest restoration. While carbon sequestration is a major objective, the case for restoration often includes benefits to local communities. However, the impacts of forest restoration on local hydrological services (e.g. flood and erosion risk, stream flow during dry periods) are surprisingly poorly understood. Particularly limited information is available on the impacts of passive tropical forest restoration following shifting cultivation. The outcome depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 53 publications
(57 reference statements)
2
21
0
Order By: Relevance
“…The variation in K s for AR indicates that locally IOF will occur, but this flow may infiltrate at locations where the values are much higher (mean K s of 240 mm h −1 , standard deviation 212), and it is unlikely that IOF will occur at RF (mean K s of 324 mm h −1 , standard deviation 173 mm h −1 ). The latter is in line with research elsewhere [15,16,23,24]. To have a better understanding of hillslope scales it is recommended to apply larger scale measurements of overland flow, subsurface processes, and precipitation measurements.…”
Section: Infiltration Characteristics and Implications For Runoff Processessupporting
confidence: 58%
See 1 more Smart Citation
“…The variation in K s for AR indicates that locally IOF will occur, but this flow may infiltrate at locations where the values are much higher (mean K s of 240 mm h −1 , standard deviation 212), and it is unlikely that IOF will occur at RF (mean K s of 324 mm h −1 , standard deviation 173 mm h −1 ). The latter is in line with research elsewhere [15,16,23,24]. To have a better understanding of hillslope scales it is recommended to apply larger scale measurements of overland flow, subsurface processes, and precipitation measurements.…”
Section: Infiltration Characteristics and Implications For Runoff Processessupporting
confidence: 58%
“…Recent literature reviews have indicated that tree planting in the tropics can improve the water infiltration in degraded soils [3,7,15,16]. Most field studies in forests undergoing restoration [8,[17][18][19][20][21] have measured water infiltration on the top-oil focusing on the saturated soil hydraulic conductivity (K s ), only a few scientific works [22][23][24][25][26] have investigated the preferential flow pathways, explaining the water movement through the soil profile. Usually, preferential flow pathways are identified by dye tracer experiments, which have been important in hydrology to understand the water cycle, subsurface flows, and transport processes [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Natural regeneration can also provide many ecosystem service benefits, including hydrological regulation 39,40 (Figure 3C) (A) The Great Green Wall initiative aims to reduce land degradation, improve climate adaptation, and strengthen food security by restoring arid-resistant landscapes in a $15 km wide belt across 7,775 kilometres of Africa. Costing $US$43 billion by completion, 16% of the project was underway in 2020 8 .…”
Section: Restoration Of Abandoned Farmlandmentioning
confidence: 99%
“…Error bars indicate 95% confidence intervals; effects are significant (P < 0.05) if confidence interval does not overlap zero. Plots redrawn from: (A) 19 ; (B) 32 ; (C) 39 ; and (D) 54 ; data from 40 .…”
Section: Synergies and Trade-offs In Delivering Restoration Outcomesmentioning
confidence: 99%
See 1 more Smart Citation